Antioxidant, neuroprotective and anti-inflammatory activity of Curcuma longa extracts: from green extraction to nanoemulsion - Perez, Adriana; Martinez-Correa, Hugo A.; Parada-Alfonso, Fabiãn; Suárez Montenegro, Zully Jimena; Ballesteros-Vivas, Diego; Álvarez-Rivera, Gerardo; Cifuentes, Alejandro; Ibáñez, Elena (Frontiers in Nutrition, 2025)
Turmeric rhizomes are rich in bioactive compounds like curcuminoids, offering antioxidant and anti-inflammatory properties. It is a medicinal plant aiding in the prevention of neurological, cardiovascular, and metabolic diseases. In the present study, the sequential extraction of turmeric (Curcuma longa L.) combining supercritical fluid extraction (SFE) followed by ultrasound-assisted extraction (UAE) has been described for the first time to improve the yield and bioactivity of the different fractions. In the SFE stage, the maximum oil extraction yield (4.0%) was obtained; under these conditions, maximum bioactives’ content was obtained. In the UAE stage, the total phenolic content (TPC), curcuminoids, antioxidant capacity (DPPH, ABTS), inhibitory activity against the acetylcholinesterase enzyme (AChE), and against the lipoxygenase enzyme (LOX) were analyzed, together with a complete profile by UHPLC-qTOF-HRMS in order to tentatively identify the compounds responsible of the observed bioactivities. The UAE process resulted in a maximum TPC of 181.51 mg GAE/g DE, CUR of 604.40 mg/g DE, highlighting a high inhibitory potential for AChE (IC50: 5.21 μg/mL) and LOX (IC50: 17.96 μg/mL). A nanoemulsion of the obtained extract showed no significant changes after 15 days, indicating good stability and homogeneous particle distribution. The SFE + UAE combination enhances yield and concentration of bioactive compounds like phenols and curcuminoids, optimizing turmeric extract’s neuroprotective and anti-inflammatory potential and providing fractions with specific composition of bioactives, thus targeting different health benefits. In this sense, both fractions could be advantageously employed to develop nutraceuticals and/or functional foods with specific health benefits.